(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The subject company is a retail manufacturing company that caters to the needs of local and international households. The continuing growth of the company had to do with the underlying vision of the founder, who envisioned that the Philippines should be an exporter not only of skilled workers and nurses in the Middle East but also as entrepreneurs. The retail manufacturing industry is approximately 27 years in the industry and has a multimillion-dollar company with a market presence in over 29 countries and is involved in a plethora of business interests from manufacturing and soon to conquer the real estate and has incorporated the use of digital marketing in demonstrating their products via live demonstration on social media platforms. The researchers interviewed the HR Supervisor for collecting relevant information that the researchers may be able to use during the policy development. The researchers asked for permission to have a copy of the current policy of the company to develop a new policy, enhance the current and update some current policies. The researchers also used online resources, books, and journalsas references beforedeveloping a policy. According to the gathered information coming from the HR Supervisor, The retail manufacturing industry implemented the following policy: Attendance and Punctuality Policy, Employee Accountability and Clearance Policy, Employee Financial Assistance Policy –Calamity/Bereavement, Employee Financial Assistance Policy –CA for Financial Assistant Assignment, Employee BenefitsPolicy –Free Uniform, Employee Last Pay Policy, Performance Management Policy, Job Description Key Objectives and Key Result Areas, and Code of Discipline. The researchers perceived that the retail manufacturing industry will benefit if they will implement a No-Gift Policy, Anti-Age Discrimination Policy for the Standard of Conduct, Data Privacy Policy and Enhancement of Records for Human Resource InformationManagement, Solo Parent Leave for Compensation and Benefits. Assimilation Program for Recruitment, Placement and Retention, Internship Program for Contractual Arrangement, Lactation Program and Lactation Area for Staff Well-Being, Training Program for Product Demonstration, Promotion, Job Rotation and Performance Management for Career Management, Open Door Policy, and Duties and Responsibilities and Penalty for No-Gift Policy for Good Governance. The proposed policies by the researchers aimed to benefit the employees and employers.